Biconidium sinense gen. et sp. nov. (Hypocreales, Bionectriaceae) and Didymocyrtis shanxiensis sp. nov. (Phaeosphaeriaceae, Didymocyrtis) isolated from urban soil in China - Hai-Yan Wang; Chunbo Dong; Yan-Wei Zhang; Wan-Hao Chen; Yan-Feng Han (MycoKeys)
During a fungal diversity survey in various urban habitats across China, 5 fungal isolates were discovered from soil samples. Detailed morphological observations and multi-gene phylogenetic analyses confirmed the identification of two novel taxa: Biconidium sinense gen. et sp. nov. and Didymocyrtis shanxiensis sp. nov. These species were formally described, illustrated, and discussed, highlighting their distinct characteristics and taxonomic placement. The study expands our understanding of fungal diversity in urban environments, emphasizing the importance of combining morphological and molecular approaches for accurate species delineation and discovery.